Gritty and habitual : research on the theory of planned behavior and autonomous motivation for physical activity in adolescents - Choi, Jinyoung (2019)
Grit is perseverance and passion for long-term goals, an individual trait that can lead to successful outcome. Habit is considered as goal-directed automaticity, repeated with low awareness, which may interact with behavior and intention for the behavior. The theory of planned behavior (TPB) describes constructs in predicting behavior with the intention to act. There have been several studies on each of the three elements mentioned above (grit, habit, TPB) and autonomous motivation in physical activity (PA). However, few studies look at the relationship altogether between these variables. This study examined the associations of psychological constructs based in the TPB with grit and habit. As a pilot study of a larger project, the study aims to examine if individual differences in grit and habit can predict intentions and behavior of PA. It was hypothesized that grit and habit will both have effect on PA and the TPB variables. 277 Finnish secondary school students (grades 7, 8 and 9) were asked to fill out a questionnaire at two points in time (week 1 and 5). The questionnaire contained questions from three different questionnaires that measure grit (Duckworth & Peterson, Matthews & Kelly, 2007), habit (Gardner et al., 2012), and the constructs of the TPB (Ajzen, 1985). Reliabilities were analyzed with Cronbach’s α and the correlational coefficient r. The relationships between the variables were quantitatively measured through correlational and regression analysis using SPSS. Correlations revealed that grit and habit correlated each in varying degrees to attitude, subjective norms, perceived behavioral control, intention and PA. Longitudinal correlations were found especially with habit, intention, and PA (r ≥ .20). Grit had small longitudinal correlation with PA (r = .13). ANOVA results indicated that students with higher grit or higher automaticity were more physically active in both Time 1 and 2. There were no combined effects of grit and habit on PA. Regression results demonstrated the cross-sectional and longitudinal effect of grit and habit on PA, with intention as a mediating variable. Grit and habit are considered as important predictors to physical activity of adolescents, and as suitable targets for intervention. The results of the study will be important in understanding the effect of grit and habit on the variables of autonomous motivation in the TPB.